GIVING RED RICE (ORIZA NIVARA) TO CHANGE GLUCOSE LEVELS IN DIABETES MELLITUS PATIENTS IN KENDARI CITY: Red Rice to Change Glucose Levels - Ardiansyah, Laode; Nawawi (Universitas Mandala Waluya Kendari, 2020)
Background:Diabetes mellitus (DM) is a phenomenon which the body cannot produce insulin supply which is indicated by increasing blood glucose levels. Red Rice (Oriza nivara) contains flavonoid compounds which have antidiabetic abilities. It can reduce blood glucose by increasing insulin secretion and preventing insulin resistance. This study aims to determine the effect of giving brown rice (Oriza nivara) to change blood glucose levels in people with diabetes mellitus in Kendari City. Methods: This research method was carried out with a quasi-experimental design with pre-post test design for 1 week with primary and secondary data collection techniques. The respondents were determined by proportional random sampling. Respondents in this study were 33 people with DM. Result:The results of the study on checking blood glucose levels before and after giving brown rice (oriza nivara) within 1 week obtained P value = 0.000 < alpha 0.05. Conclusion: there is a significant effect of giving brown rice (oriza nivara) on changes in blood glucose level in diabetes mellitus people in Kendari City.